Superfluorinated Ionic Liquid Crystals Based on Supramolecular, Halogen‐Bonded Anions. (13th April 2016) - Cavallo, Gabriella; Terraneo, Giancarlo; Monfredini, Alessandro; Saccone, Marco; Priimagi, Arri; Pilati, Tullio; Resnati, Giuseppe; Metrangolo, Pierangelo; Bruce, Duncan W.
Abstract: Unconventional ionic liquid crystals in which the liquid crystallinity is enabled by halogen‐bonded supramolecular anions [C n F2  n +1 ‐I⋅⋅⋅I⋅⋅⋅I‐C n F2  n +1 ] − are reported. The material system is unique in many ways, demonstrating for the first time 1) ionic, halogen‐bonded liquid crystals, and 2) imidazolium‐based ionic liquid crystals in which the occurrence of liquid crystallinity is not driven by the alkyl chains of the cation.